1994
DOI: 10.1002/cne.903440309
|View full text |Cite
|
Sign up to set email alerts
|

Localization of nerve growth factor (NGF) and low‐affinity NGF receptors in touch domes and quantification of NGF mRNA in keratinocytes of adult rats

Abstract: Touch domes are clearly delineated mechanoreceptors that are visible on the depilated skin of mammals. These structures consist of a sharply circumscribed disk of thickened epithelium surmounting a group of Merkel cells that are innervated by type I sensory neurons. These characteristic cutaneous structures provide an ideal opportunity for investigating whether the localization of nerve growth factor (NGF) in the skin is related to sites of sensory axon termination. For these reasons, we have used immunocytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…Conversely, over-expression of NT-3 in the epidermis led to a 42% increase in the number of dorsal root ganglion neurons and a concommitant increase in Merkel cell numbers in touch domes by 4 -8 months of age (Albers et al, 1996). These data and denervation studies (Burgess et al, 1974;English et al, 1980English et al, , 1994 suggest that a trophic factor, such as NT-3, that is released by nerve terminals supports postnatal Merkel cell survival (reviewed by Saxod, 1996). We can exclude NT-3 as a neuronderived trophic factor, as we find high levels of NT-3 in Merkel cells themselves and in neighboring epithelial cells in the outer root sheath.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Conversely, over-expression of NT-3 in the epidermis led to a 42% increase in the number of dorsal root ganglion neurons and a concommitant increase in Merkel cell numbers in touch domes by 4 -8 months of age (Albers et al, 1996). These data and denervation studies (Burgess et al, 1974;English et al, 1980English et al, , 1994 suggest that a trophic factor, such as NT-3, that is released by nerve terminals supports postnatal Merkel cell survival (reviewed by Saxod, 1996). We can exclude NT-3 as a neuronderived trophic factor, as we find high levels of NT-3 in Merkel cells themselves and in neighboring epithelial cells in the outer root sheath.…”
Section: Discussionmentioning
confidence: 74%
“…Conversely, NT-3 over-expression in the epidermis leads to a significant increase in the number of dorsal root ganglion sensory neurons and an increase in Merkel cells per touch domes in the periphery, indicating that NT-3 is involved in the regulation of the final number of sensory neurons and Merkel cells (Albers et al, 1996). Immunohistochemical studies of p75NTR immunoreactivity in the skin of adult rats (Ribeiro-da-Silva et al, 1991;English et al, 1994) and the fetal human footpad (Narisawa et al, 1992) showed p75NTR immunoreactivity in Merkel cells in touch domes of the basal epidermis. p75NTR immunoreactivity is seen in the outer root sheath of the hair follicle at postnatal age day 3-6 of murine back skin (Botchkareva et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that neurotrophins produced in or around taste buds bind directly to p75 receptors and influence taste buds via autocrine or paracrine mechanisms. This type of nerve-independent mechanism functions to maintain adult Merkel cells (English et al, 1994;Kinkelin et al, 1999;SieberBlum et al, 2004). However, it is unlikely that neurotrophins act directly on taste buds via p75, since unlike previous reports (Fan et al, 2004;Yee et al, 2005), no p75-like immunoreactivity was observed in taste cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking p75 (p75 À/À ) have sensory neuron and receptor deficits and develop periodic lesions on their footpads (Lee et al, 1992). A specific receptor complex, comprised of specialized p75 receptor expressing cells of the epidermis known as Merkel cells (English et al, 1994;Szeder et al, 2003;Sieber-Blum et al, 2004) and slowly adapting type 1 (SA1) mechanosensory neurons, requires the p75 receptor for its maintenance during late postnatal development (Fundin et al, 1997;Stucky and Koltzenburg, 1997;Rice et al, 1998;Kinkelin et al, 1999). In p75 À/À animals, Merkel cells are lost between 2 weeks and 2 months of age (Fundin et al, 1997;Kinkelin et al, 1999;Cronk et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation